Advanced blood and neuroimaging biomarkers of axonal injury after TBI in the prospective multi-centre BIO-AX-TBI study. Issue 6 (27th May 2022) - Graham, Neil; Zimmerman, Karl; Moro, Federico; Gradisek, Primoz; Magnoni, Sandra; Oddo, Mauro; Zetterberg, Henrik; Bertolini, Guido; Sharp, David; ,
Abstract : Background: Outcomes after traumatic brain injury (TBI) are variable and frequently poor. Axonal injury is considered a significant determinant of outcome, which may be quantified using novel fluid biomark- ers and advanced MRI. Methods: BIO-AX-TBI is a multi-centre cohort study of acute moderate-severe TBI. Patients underwent clinical and blood biomarker/MRI assessment over one year. Blood levels of neurofilament light (NfL), ubiquitin carboxy-terminal hydrolase L1 (UCH-L1), glial fibrillary acidic protein (GFAP), total tau and S100B were quantified, with cerebral microdialysis facilitating measures in brain extracellular fluid. Results: 197 patients were assessed post-TBI. Compared with controls, TBI patients had significant acute elevations in GFAP, S100B, tau and UCH-L1, with NfL peaking subacutely and remaining elevated. NfL in plasma and brain interstitial fluid were highly correlated in the microdialysis subgroup. Diffusion tensor imaging (DTI) showed reduced fractional anisotropy, remaining chronically abnormal post-injury. Early cortical atrophy was predicted by acute plasma tau and chronic white matter atrophy was predicted by NfL. Clinical outcomes were accurately predicted by acute blood biomarker levels and DTI MRI. Conclusions: Neuronal/glial markers in blood provided a reliable readout of TBI severity and predicted clinical outcomes. NfL and DTI MRI were highly sensitive to white matter injury and predicted chronic atrophy. neil.graham@imperial.ac.uk